REKAYASA PERANGKAT LUNAK PENGOLAHAN DATA DISTRIBUSI OBAT- OBATAN DI PT. ANUGRAH PHARMINDO LESTARI BERBASIS WEB - Yuhendra Yuhendra; Riza Eko Yulianto (Jurnal Momentum ISSN 1693-752X)
PT. Anugrah Pharmindo Lestari (APL) is a company engaged in the distribution of pharmaceuticals to be distributed to outlets (hospitals, pharmacies etc.). Currently the data processing distribution of pharmaceuticals PT. Anugrah Lestari Pharmindo done manually, in addition to the company is also difficult to assess the type of pharmaceuticals most consumers need. As for the book party of pharmaceuticals outlets should come to the company making it less effective and efficient in terms of cost and time. This study aims to build a data processing system of distribution of pharmaceuticals that can process data with good distribution and facilitate the outlet in making reservations and obtain information of pharmaceuticals data. The system is built using the programming language PHP, MySQL database and Apache webserver. With this system the data processing distribution of pharmaceuticals PT. Pharmindo Anugrah Lestari becomes easier with the purchase and sales reports. There was also a chart that is used to monitor the pharmaceuticals most needed, as well as the outlet no longer need to come to the company to order the pharmaceuticals